2017
DOI: 10.19082/4597
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms associated with gastroesophageal reflux disease, and their relapses after treatment with proton pump inhibitors: A systematic review

Abstract: Gastroesophageal reflux disease (GERD) is a common functional gastrointestinal disorder with significant effects on the quality of life. The burden of GERD is soaring in Asia. Preventing symptom relapse is a therapeutic goal in GERD patients. Since proton pump inhibitors (PPI) are the first-line treatment of GERD, drug failure has become a major problem in the treatment procedure. We reviewed the literature in order to find articles related to comorbidities and symptoms affecting GERD from 1980 to 2015 via Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Antacids, alginates, histamine (H 2 ) receptor blockers, or proton pump inhibitors (PPIs) are typically a first-line medical treatment for patients with GERD [ 1 , 38 - 40 ]. In recent years, PPIs, e.g., omeprazole, which work by covalently binding to the proton pumps that control the final step of gastric acid production, thereby decreasing it, have become the treatment of choice for patients with GERD, with a number of studies showing superiority over H 2 receptor blockers [ 5 , 38 , 41 - 49 ]. Typically, a standard dose of a PPI provides complete relief in approximately 70 to 80% of patients with GERD within a week [ 1 , 50 - 53 ], with limited differences in effectiveness between twice-daily and once-daily PPIs [ 54 ].…”
Section: Reviewmentioning
confidence: 99%
“…Antacids, alginates, histamine (H 2 ) receptor blockers, or proton pump inhibitors (PPIs) are typically a first-line medical treatment for patients with GERD [ 1 , 38 - 40 ]. In recent years, PPIs, e.g., omeprazole, which work by covalently binding to the proton pumps that control the final step of gastric acid production, thereby decreasing it, have become the treatment of choice for patients with GERD, with a number of studies showing superiority over H 2 receptor blockers [ 5 , 38 , 41 - 49 ]. Typically, a standard dose of a PPI provides complete relief in approximately 70 to 80% of patients with GERD within a week [ 1 , 50 - 53 ], with limited differences in effectiveness between twice-daily and once-daily PPIs [ 54 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, patients with long-term medication need to be alert and monitored for adverse drug reactions. Evidence (Hosseini et al, 2017) shows that even if PPI is gradually reduced during the course of treatment, the recurrence rate does not change much in the short term, whereas the corresponding gastrointestinal symptoms will increase, such as dyspepsia and irritable bowel syndrome. In addition, recent large-scale association studies based on the evaluation of prescription databases (Gyawali, 2017) have shown that the long-term use of PPI can lead to adverse reactions such as bacterial gastroenteritis, microscopic colitis, acute interstitial nephritis, fundic gland polyps, and hypomagnesemia.…”
Section: Introductionmentioning
confidence: 99%
“…Because current conventional drug treatment mainly addresses the symptoms rather than the pathogenesis, the drugs for treating NERD are constantly updated, but the treatment effect is not satisfactory. A study by Yu et al ( 18 , 19 ) shows that the combination of conventional drugs (esomeprazole) with antidepressants or anxiolytics (flupentixol and melitracen) in the treatment of GERD was superior to esomeprazole alone. However, clinical trials have shown that the side effects of even low doses of antidepressants and anti-anxiety drugs limit the widespread use of this combination for the treatment of NERD.…”
Section: Introductionmentioning
confidence: 99%